The Potency of Teter Leaf Herbal Tea as a Functional Beverage Based on Drying Time - Putra, I Gede Arie Mahendra; Dewi, Putu Julyantika Nica; Dewi, I Gusti Agung Bulan Mutiara; Devani, Made Dita Dewi; Wahyuniari, Ida Ayu Tisna; Saraswati, I Gusti Ayu Krisma Widya (International Journal on Food, Agriculture and Natural Resources, 2025)
The teter plant is an herbal plant cultivated in Taro Village, rich in bioactive components with various health benefits, especially in its leaves. Taro villagers process teter leaves into a product called ‘loloh’ don teter. However, this product has the disadvantage of a short shelf life and is less desirable to the general public. As a solution, teter leaves can be processed into herbal tea. One important aspect in making herbal tea is the drying time. This study aimed to determine the effect of drying time on the Teter Leaf Herbal Tea characteristics and to obtained the appropriate drying time in making Teter Leaf Herbal Tea and its potential as a functional beverage. A Completely Randomized Design (CRD) was used with the treatment of drying time at 4 levels (12; 18; 24; and 30 hours at 50oC). The results showed that the drying time had a significant effect on the characteristics of Teter Leaf Herbal Tea. A drying time of 24 hours was the right time to produced herbal tea with a yield of 20.74%, moisture content of 7.21%, total phenols 40.71 mg GAE/g, total flavonoids 28.76 mg QE/g, total tannins 0.80 mg TAE/g, vitamin C 8.13 mg AAE/g, and antioxidant activity of 85.55%. Teter leaf has the potential to be developed into functional beverage.